A Method for Collecting Atmospheric Microbial Samples From Set Altitudes for Use With Next-Generation Sequencing Techniques to Characterize Communities - Allison M Spring; Kathryn M Docherty; Kenneth D Domingue; Thomas V Kerber; Margaret M Mooney; Kristina M Lemmer (Air, Soil and Water Research, 2018)
Dispersal of airborne microorganisms is an important ecological process, resulting in the distribution of bacteria to all habitats on Earth. Investigation of this process is limited by the ability to collect uncontaminated high-altitude microbial samples for use with next-generation sequencing approaches. Here, we describe the design of a Remote Airborne Microbial Passive sampling system. Troubleshooting experiments demonstrate that the samplers collect adequate DNA for bacterial 16S rRNA (ribosomal RNA) amplicon–based Mi-Seq sequencing at 2 and 150 m from the ground. When samplers are closed, they retain only a low number of sequences, and may be used as a negative control. We also demonstrate that the optimal amount of collection dishes to include in the sampler is 8, and that freezing collection dishes at −80°C is an alternative to immediate DNA extraction. Samplers may be used to address a variety of ecological and human health–related questions.